TARI JARANSARI DALAM UPACARA RITUAL BERSIH DESA LENCOH KECAMATAN SELA BOYOLALI - Setyoasih, Sri; Setiyastuti, Budi; Nuryanto, Nuryanto; Samsuri, Samsuri; Daryono, Daryono (Institut Seni Indoensia Surakarta, 2022)
ABSTRACT Jaransari dance to cleanse the village of Lencoh, Sela, Boyolali is an art with a ritual function. There is a relationship between dance and local cultural customs. The research objective is to explore the art of dance with local cultural traditions.This research uses an anthropological approach to dance that is qualitative and descriptive. The methods used include observation, interviews, documentation, and literature.The result that the Jaransari dance desired to achieve is a folk dance performed in village cleansing ritual activities. Dance activities are closely related to the lifestyle of the community to deal with critical situations from the influence of the power of the village guardian spirits. Through the activities of the Jaransari dance, the community is considered to have fulfilled the wishes of the village's spirit, so that it will not interfere with community activities. After the cleansing ritual ceremony of the village, the community calmed down, worked hard and the harvest was bountiful.Key Words: jaransari, folk dance, ritual, village cleansing ABSTRAKTari Jaransari dalam rangka bersih desa Lencoh, Sela, Boyolali merupakan seni yang berfungsi ritual. Terdapat hubungan antara seni tari dengan adat budaya setempat. Tujuan penelitian adalah untuk menggali seni tari dengan adat budaya setempat.Penelitian menggunakan pendekatan antropologi tari yang bersifat desktiptif kualitatif. Metode yang digunakan meliputi observasi, wawancara, dokumentasi dan kepustakaan. Hasil yang ingin dicapai tari Jaransari merupakan tari rakyat yang dipertunjukan pada kegiatan ritual bersih desa. Kegiatan tari berkaitan erat dengan pola hidup masyarakat untuk menghadapi situasi gawat dari pengaruh kekuatan goib penunggu rokh desa. Melalui kegiatan tari Jaransari masyarakat dianggap telah memenuhi keingginan penunggu rokh desa sehingga tidak mengganggu aktivitas masyarakat. Setelah upacara ritual bersih desa masyarakat menjadi tenang, giat bekerja dan panen melimpah.Kata Kunci: jaransari, tari rakyat, ritual, bersih desa.